Question #457c7?

2 Answers
Nov 22, 2017

Jason had 84 $ and Wilson had 91 $

Explanation:

Let Jason have 12x $ and Wilson 13x$. After spending 63$ , he will have 13x-63 $ with him.

The situation now is that 12x $ is 3 times of (13x-63)$. Putting it in equation form, it would be
12x= 3* (13x-63) -> 12x= 39x-189-> 27x=189 -> x=7

This means that at the beginning Jason had 84$ and Wilson had #91$
***

Nov 22, 2017

Wilson originally had $91

I have taken you to a point where you should be able to finish off.

Explanation:

color(blue)("Setting up the given information")Setting up the given information

Let Jason's original money be represented by jj
Let Wilson's original money be represented by ww

Using ratio in fraction format

Then initial condition

j/w=12/13 color(white)("ddd")->color(white)("ddd") j=12/13w" ".........Equation(1)

But Wilson spent $63 changing the ratio to:

j/(w-63)=3/1color(white)("ddd")->color(white)("ddd")j=3w-189" "..Equation(2)

Using Eqn(2) substitute for j" in "Eqn(1)

color(green)(color(red)(j) =12/13wcolor(white)("ddd")->color(white)("ddd")color(red)(3w-189)=12/13w )

color(green)(color(white)("dddddddddd")->color(white)("ddd")27/13w=189)

color(white)("dddddddddd")->color(white)("dddddd")color(blue)(w=$91)
~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~

Substitute for w in Equation(1) to find Jason's original sum of money.